Clinical correlation between serum uric acid level and tophus involmente of tendon: a descriptive study - Soni, Susheel; Mantri, Deepak; Agrawal, Penosh (International Journal of Research in Orthopaedics, 2018)
Background: Clinical correlation between serum uric acid level and tophus involvement of tendon. Methods: This is a non randomised multicetric prospective study carried out from December 2015 to May 2018. This is a descriptive study comprising 108 patients with diagnosis of gout according to the American College of Rheumatology (ACR) criteria. US examination included the quadriceps tendons, the patellar Tendon, peroneus tendon and the Achilles tendon. All tendons were evaluated bilaterally according to the EULAR guidelines for performing US in rheumatology. Results: We included the patients aged between 20-60 year. In this study male patients was 86 (79.63% ) and 22 (20.37%) patient were female. In this study 108 patients with serum uric acid level between 5.5 -9.0 mg/dl with age from 20 yr to 60 yr were studied. Uric acid level between 7 - 9 mg/dl found in 68.48% and it was in age between 30–45 yr of age. 73 patiens (67.59%) had pain at enthesis for at least once before inclusion in the study. Intra-tendinous tophi and hyperechoic aggregates were the most frequent lesions at the tendon in US examinations. In our study Patellar tendon is the most frequently involved tendon followed by quadriceps, Achilles and peroneus tendon. Conclusions: Tophius involvement of tendon in the lower limbs in gout is very frequent, particularly at the patellar tendon, Quadriceps tendon and Achilles tendon.